Capitalism's last stand? : deglobalization in the age of austerity - Bello, Walden, 1954- (Zed Books, 2013)
"In this eye-opening and often scathing book, Walden Bello provides a forensic dissection of contemporary capitalism's multiple crises. Trenchant but constructive, Bello's analysis of the collapse of the global real economy - covering such issues as the Wall Street meltdown, the disintegration of the Greek economy and the rise of China - emphasizes the ever more pressing need to engage in a radical process of 'deglobalization' towards a decentralized, pluralistic world system. Only then will we be able to construct a fairer and more equitable society."--Zadní strana obálky
Keywords: 21. století; mezinárodní hospodářské vztahy -- 21. století; světová ekonomika -- 21. století; globalizace -- 21. století; kapitalismus -- 21. století; international economic relations -- 21st century; world economics -- 21st century; globalization -- 21st century; capitalism -- 21st century; eseje; essays